2021
DOI: 10.4103/aian.aian_441_20
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pain-Related Evoked Potential in the Diagnosis of Meralgia Paresthetica

Abstract: Introduction: Entrapment of the lateral femoral cutaneous nerve (LFCN) of thigh results in meralgia paresthetica (MP). Standard electrophysiological tests for MP are technically demanding and unreliable. We aimed to study the role of pain-related evoked potentials (PREP) in the diagnosis of MP. Methods: Patients with MP and normal volunteers were included. PREP was recorded by stimulating the skin over the lateral thigh 20 cm below the anterior-superior iliac spine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…There is currently interest in developing PREPs with noninvasive electrical stimulation for indexing nociceptive Aδ fibers. Utility of the concentric planar electrode has been reported in the screening of mixed and single fiber polyneuropathies, 54 meralgia paraesthesica, 55 and central nervous system disease. 56 Work is in progress to improve techniques to activate Aδ fibers.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently interest in developing PREPs with noninvasive electrical stimulation for indexing nociceptive Aδ fibers. Utility of the concentric planar electrode has been reported in the screening of mixed and single fiber polyneuropathies, 54 meralgia paraesthesica, 55 and central nervous system disease. 56 Work is in progress to improve techniques to activate Aδ fibers.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Shaikh AI and colleagues [6], it was interpreted that the role of pain can be recorded related to somatosensory-evoked potentials (SSEPs) in the diagnosis of paresthesia meralgia and, in addition, show latency in the electrophysiological study [7,8]. For a better sensitivity and specificity of the test, it is necessary to carry out the test by an experienced • Sequels of surgery: Orthopedist surgeries involving the pelvis may damage the nerve due to anatomical variations.…”
Section: Meralgia Parestheticamentioning
confidence: 99%
“…However, both studies recommend the association of SSEP and sensory NCS for a comprehensive and accurate assessment of MP patients. PREP is a relatively new technique, having an AUC = 0.97, with a sensitivity of 91.7% and a specificity of 100% for MP diagnosis [67]. Thus, although sensory NCS studies were considered to be superior EDX methods, recent studies have concluded that modern techniques such as SSEP and PREP provide better accuracy [66,67].…”
Section: Electrodiagnostic and Imaging Techniquesmentioning
confidence: 99%